Expression and function of aquaporins in peripheral nervous system - Ma Tong-hui; Gao Hong-wen; Fang Xue-dong; Yang Hong (Acta Pharmacologica Sinica; Vol 32, No 6 (June 2011): Acta Pharmacologica Sinica(Special Feature:Channelopathy and drug discovery）, 2016)
The expression and role of the aquaporin (AQP) family water channels in the peripheral nervous system was less investigated. Since 2004, however, significant progress has been made in the immunolocalization, regulation and function of AQPs in the peripheral nervous system. These studies showed selective localization of three AQPs (AQP1, AQP2, and AQP4) in dorsal root ganglion neurons, enteric neurons and glial cells, periodontal Ruffini endings, trigeminal ganglion neurons and vomeronasal sensory neurons. Functional characterization in transgenic knockout mouse model revealed important role of AQP1 in pain perception. This review will summarize the progress in this field and discuss possible involvement of AQPs in peripheral neuropathies and their potential as novel drug targets.